Study on Seismotectonic b-value and Dc Value for Dolakha after Gorkha Earthquake 2015 - Shrestha, Prakash M.; Gupta, Suresh P.; Adhikari, Binod; Rai, Krishna B. (Patan Pragya, 2022)
Fractal correlation dimension (Dc) and the b-value methods are being used in this study with the earthquakes (m l ≥ 4.0) for the period 2015/4/25 to 2016/10/7 in Dolakha district after Gorkha Earthquake, 2015. The entire data have been divided into 3 windows each with consecutive fifty events for observing temporal variation of Dc value and b value. Low b value of 0.87± 0.05 is found during the period between 2015/4/25 to 2015/5/14 (window 1), indicates the large earthquakes of the period. The large earthquake of magnitude (m l ) of 6.8 is seen to occur 2015/5/12 in the study region in window 1. High b value of 1.53± 0.14 is found during the period from 2015/6/22 to 2016/10/7. The Dc value varies from 1.10 to 1.17 indicating the clustering phenomena of the events during the period. Thus, this kind of clustering pattern study by using local station data for Dolakha can help in the preparedness and mitigation of earthquake hazard.